Childhood Onset Psychosis: A Case Report - Jha, A; Kunwar, A; Dhonju, G (Journal of Psychiatrists’ Association of Nepal, 2020)
Childhood psychosis is an extremely rare condition. We describe the case of 6.5 yr old male child who presented with symptoms suggestive of psychosis and later responded well to antipsychotic clozapine. This case study reveals that the identification of very early onset psychosis is challenging and treatment is crucial for prevention of long-term disability.